Analysis of Personnel Management Strategy in Improving Human Resources Performance in Sharia Banking - Fitri, Zakiyyah Nur; hasan, Asyari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Banking is one of the institutions engaged in finance that plays a role in efforts to advance the country’s economy. As an institution whose role is to advance the country’s economy, the performance of employees at the institution is highly valued. In this assessment, there is a strategy that has been determined by the personnel management to improve the performance of these human resources. The study aims to determine how the personnel management strategy in an effort to improve employee performance at Bank Muamalat Bengkulu Branch office. This research is field research, with a qualitative research approach. It uses a purposive sampling technique, namely the technique of sampling data sources based on certain considerations. The researchers made employees at Bank Muamalat Bengkulu Branch Office as subjects/informants a total of 5 people. Based on the results of the study, it can be concluded that the personnel management strategy in an effort to improve the performance of human resources at Bank Muamalat Bengkulu Branch Office is carried out independently, in class, and periodically trained.